2019
DOI: 10.1051/0004-6361/201833821
|View full text |Cite
|
Sign up to set email alerts
|

The origin of radio emission in broad absorption line quasars: Results from the LOFAR Two-metre Sky Survey

Abstract: We present a study of the low-frequency radio properties of broad absorption line quasars (BALQSOs) from the LOFAR Two-metre Sky-Survey Data Release 1 (LDR1). The value-added LDR1 catalogue contains Pan-STARRS counterparts, which we match with the Sloan Digital Sky Survey (SDSS) DR7 and DR12 quasar catalogues. We find that BALQSOs are twice as likely to be detected at 144 MHz than their non-BAL counterparts, and BALQSOs with low-ionisation species present in their spectra are three times more likely to be dete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 129 publications
12
26
0
Order By: Relevance
“…By investigating the radio properties of Sloan Digital Sky Survey (SDSS) DR7 quasars from the Faint Images of the Radio Sky at Twenty-Centimetres (FIRST) survey (Becker, White & Helfand 1995), Richards et al (2011) were able to show that radio-loud quasars are concentrated at low C IV blueshifts, thus suggesting radio-loud quasars often have little to no outflowing wind. This behaviour is broadly consistent with the relative scarcity of radio-loud BAL quasars (Stocke et al 1992;Becker et al 2000;White et al 2007;Morabito et al 2019). Richards et al (2011) also found radio-quiet quasars with low blueshifts and, in fact, very similar UV spectral energy distributions (SEDs) to the radio-loud quasars.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…By investigating the radio properties of Sloan Digital Sky Survey (SDSS) DR7 quasars from the Faint Images of the Radio Sky at Twenty-Centimetres (FIRST) survey (Becker, White & Helfand 1995), Richards et al (2011) were able to show that radio-loud quasars are concentrated at low C IV blueshifts, thus suggesting radio-loud quasars often have little to no outflowing wind. This behaviour is broadly consistent with the relative scarcity of radio-loud BAL quasars (Stocke et al 1992;Becker et al 2000;White et al 2007;Morabito et al 2019). Richards et al (2011) also found radio-quiet quasars with low blueshifts and, in fact, very similar UV spectral energy distributions (SEDs) to the radio-loud quasars.…”
Section: Introductionsupporting
confidence: 75%
“…With the advent of the highsensitivity Low-Frequency Array (LOFAR; van Haarlem et al 2013), it is now possible to probe the radio-quiet population in more detail (e.g. Gürkan et al 2015Gürkan et al , 2018Gürkan et al , 2019Morabito et al 2019;Rosario et al 2020). By combining LOFAR data with the C IV emission line, we can therefore consider the relative contributions of winds, star formation, and compact jets in the radio-quiet population and their relation to disc and outflow processes.…”
Section: Introductionmentioning
confidence: 99%
“…An enhanced fraction of broad absorption line QSOs (BALQ-SOs; known to host powerful winds) have been found in red QSOs (Urrutia et al 2009), which could be evidence that red QSOs are more wind dominated than typical QSOs. Although BALQSOs are virtually all radio-quiet, they have also been found to show a remarkably similar enhancement in the radio as that found for red QSOs (Klindt et al 2019;Morabito et al 2019). Further corroborating but independent evidence for wind-dominated sources becoming more relevant at lower R values comes from Mehdipour & Costantini (2019), who showed a significant inverse correlation between the X-ray measured column density of the ionised wind in AGN and the radio-loudness parameter.…”
Section: S82 14 Ghzmentioning
confidence: 61%
“…LoBAL features are observed when the sightlines traverse denser, lower ionization state regions of the wind. LoBAL quasars, and particularly FeLoBAL quasars, are known to systematically differ from the rest of the BAL quasar population (Urrutia et al 2009;Lazarova et al 2012;Dai et al 2012;Morabito et al 2019) and may correspond to a particular evolutionary stage of quasars (e.g. Farrah et al 2007).…”
Section: Inclination Effects and Bal Sightlinesmentioning
confidence: 99%